Draconarius manus sp. nov., the third species of D. pseudocoreanus-group from China (Araneae: Agelenidae) - Wang, Yan-Chao; Zhang, Zhi-Sheng (Zootaxa, 2018)
Draconarius Ovtchinnikov, 1999 in the subfamily Coelotinae is the largest genus of the spider family Agelenidae and comprises 246 described species, mainly from East and Southeast Asia (World Spider Catalog 2018). The recently published volume on Chinese spiders in the Fauna Sinica series recorded a total 174 species of Draconarius in China, including 27 new species (Zhu, Wang & Zhang 2017).